2021
DOI: 10.1002/cbic.202100321
|View full text |Cite
|
Sign up to set email alerts
|

Surface Density of Ligands Controls In‐Plane and Aggregative Modes of Multivalent Glycovesicle‐Lectin Recognitions

Abstract: Glycovesicles are ideal tools to delineate finer mechanisms of the interactions at the biological cell membranes. Multivalency forms the basis which, in turn, should surpass more than one mechanism in order to maintain multiple roles that the ligand‐lectin interactions encounter. Ligand densities hold a prime control to attenuate the interactions. In the present study, mannose trisaccharide interacting with a cognate receptor, namely, Con A, is assessed at the vesicle surface. Synthetic (1→3)(1→6)‐branched man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Yadav et al synthesized glycovesicles prepared from diacetylene-containing glycolipid, as shown in Scheme 38. 124 Pentacosadiynoic acid (PCDA) 257 was converted to diacetylene lipids 258 and 259 by amide formation. The manno-triose headgroup 260 was coupled with the diacetylene lipid 259 through an alpha-glycoside linkage to afford the glycolipid 261 .…”
Section: Stimulus-responsive Carbohydrate Derivativesmentioning
confidence: 99%
“…Yadav et al synthesized glycovesicles prepared from diacetylene-containing glycolipid, as shown in Scheme 38. 124 Pentacosadiynoic acid (PCDA) 257 was converted to diacetylene lipids 258 and 259 by amide formation. The manno-triose headgroup 260 was coupled with the diacetylene lipid 259 through an alpha-glycoside linkage to afford the glycolipid 261 .…”
Section: Stimulus-responsive Carbohydrate Derivativesmentioning
confidence: 99%